2011
DOI: 10.1111/j.1472-4669.2011.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Pioneering fungi from the Damma glacier forefield in the Swiss Alps can promote granite weathering

Abstract: Fungi were isolated from fine granitic sediments, which were collected at 15 sampling points within a 20 m × 40 m area in front of the Damma glacier in the central Swiss Alps. From the 45 fungal isolates grown on nutrient-rich agar media at 4 °C, 24 isolates were selected for partial sequencing and identification based on the small subunit ribosomal DNA. Sequencing data revealed that the isolated fungi represented three fungal phyla and 15 species. The weathering potential of 10 of the 15 fungal species was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 60 publications
6
53
0
Order By: Relevance
“…(Tables 3-5). It is in accordance with work of other authors, who report that most abundant fungal genera isolated from rocks, and from granite in particular, were fungi from the order Mucorales, and Penicillium, Phoma, Auerobasidium, and Trichoderma (Hirsch et al, 1995;Burford et al, 2003a, b;Brunner et al, 2011). However, Ogórek et al (2013) have reported that most isolated fungus from the rocks of Niedźwiedzia Cave in Kletno is Rhizopus stolonifer.…”
Section: Pusz Et Alsupporting
confidence: 67%
“…(Tables 3-5). It is in accordance with work of other authors, who report that most abundant fungal genera isolated from rocks, and from granite in particular, were fungi from the order Mucorales, and Penicillium, Phoma, Auerobasidium, and Trichoderma (Hirsch et al, 1995;Burford et al, 2003a, b;Brunner et al, 2011). However, Ogórek et al (2013) have reported that most isolated fungus from the rocks of Niedźwiedzia Cave in Kletno is Rhizopus stolonifer.…”
Section: Pusz Et Alsupporting
confidence: 67%
“…Soil microbes play an essential role in the environment by contributing to bioavailability of nutrients from primary minerals that are required not only for their own nutrition but also for that of plants. Even in harsh conditions of glacier forefields, microbes can endure due to their mineral-weathering ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 3 abilities (Hall et al 2005;Frey et al 2010;Brunner et al 2011). Microbial weathering mechanisms include acidification, the effect of metabolites (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, inputs of C, N (as DON, nitrate and ammonium) and other nutrients (for example, sulphate and phosphate) from atmospheric deposition represent important inputs to nutrient and C pools, which are known to be small in barren soils (Bernasconi et al, 2011;Smittenberg et al, 2012). Therefore, these inputs may facilitate the establishment of pioneer microbial communities in the mineral debris (Frey et al, 2010(Frey et al, , 2013Brunner et al, 2011). The simultaneous investigation of bacterial and fungal communities present in atmospheric deposition, endogenous glacial habitats and barren soils revealed interesting patterns.…”
Section: Origin Of Microbial Pioneers In Deglaciated Soilsmentioning
confidence: 99%